Are modern contraceptives acceptable to people and where do they source them from across Nigeria? - Onwujekwe, Obinna E (BioMed Central, 2013)
BACKGROUND: Understanding the extent that different modern contraceptives are acceptable to different populations groups and where they get the commodities from will help in developing specific interventions that will help to scale-up the availability of the contraceptives. METHODS: The study took place in urban and rural sites in six states across Nigeria. Data on acceptability and sources of the contraceptives was collected from at least 770 randomly selected mostly female householders from each state respectively using a questionnaire. Acceptability of the different contraceptives was scored by the respondents on a scale of 1 (lowest) to 10 (highest). The relationships between acceptability and sources of the contraceptives with socio-economic status and geographic location of the respondents were examined. RESULTS: The use of modern contraceptives in general was acceptable to 87% of the respondents. Male condom was the most acceptable means of contraceptive with an average score of 5.0. It was followed by implants with and oral contraceptive pill with average scores of 4.0, whilst IUD was the least acceptable with an average score of 2.9. The private sector was the major source of contraceptives to different population groups. Both male and female condoms were mostly procured from patent medicine dealers (PMD) and pharmacy shops. Intra Uterine Devices (IUDs) and implants were mostly sourced from public and private hospitals in the urban areas, whilst injectibles were mostly sourced from private hospitals. Oral contraceptives were mostly sourced from pharmacy shops and patent medicine dealers. There were SES and geographic differences for both acceptability and sources of the contraceptives. Also, the sources of different contraceptives depended on the type of the contraceptive. CONCLUSION: The different contraceptives were acceptable to the respondents and the major source of the contraceptives was the private sector. Hence, public-private partnership arrangements should be explored so that universal coverage with contraceptives could be easily achieved. Interventions should be developed to eliminate the inequities in both acceptability and sources of different contraceptives. The acceptability of all the contraceptives should be enhanced with relevant behaviour change communication interventions especially in areas with the lowest levels of acceptability.